Meaning of Garuda Emblem and Relationship of City Hall Architecture in the Age of Monthon Tesaphiban : A Case Study of Monthon Tesaphiban in Isan - Pinaphang, Kritsana; Weerataweemat, Songyot (Journal of Architectural/Planning Research and Studies (JARS), 2021)
This article aimed to search the meaning of Garuda and the relationship of city hall architecture in the age of Monthon Tesaphiban in Isan area. The study was conducted by mixed method between genealogical and semiological concept. Results revealed that the Garuda emblem at the gable of city hall was regarded as a great seal of the realm affixed on such building, as same as on royal letters or other documents that needed to be affixed the seal to indicate supreme power of the king. Therefore, the city hall building was a royal representative and also made its surrounding areas be a royal territory, due to the building was located on the land and was the center of local administration that had its exact boundary. Moreover, the Garuda emblem had its meaning in cosmological concepts in Tribhumi (the tree spheres) and as a royal symbol. After installing of the Garuda emblem, the meaning of such building was adjusted to conform with new context of the governance on such territory. The building was represented the governance in absolute monarchy state and differed from the governor’s residence previously that did not represented the royal power from central administration. The building and Monthon Tesaphiban, therefore, had their meanings as the sign of royal power directly. Existence of the city hall architecture, installed with the Garuda emblem, was the establishment of royal power over surrounding areas of such building and also regarded as the microcosm at the center of such place.